Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep39318
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Mkrn2 causes abnormal spermiogenesis and spermiation, and impairs male fertility

Abstract: Although recent studies have shed insights on some of the potential causes of male infertility, new underlining molecular mechanisms still remain to be elucidated. Makorin-2 (Mkrn2) is an evolutionarily conserved gene whose biological functions are not fully known. We developed an Mrkn2 knockout mouse model to study the role of this gene, and found that deletion of Mkrn2 in mice led to male infertility. Mkrn2 knockout mice produced abnormal sperms characterized by low number, poor motility, and aberrant morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Since in vertebrates MKRN genes are highly expressed in gonads and early embryos as well, it is possible that similar molecular mechanisms are employed to regulate gene expression at these stages [33]. Consistent with this, MKRN2 was recently found to be essential for male fertility in mice [58]. Thus, our study provides a mechanism that explains the role of Mkrn1 in translation and constitutes a solid framework for future investigations deciphering the roles of vertebrate MKRNs in post-transcriptional control of gene expression during gametogenesis and early development.…”
Section: Discussionmentioning
confidence: 76%
“…Since in vertebrates MKRN genes are highly expressed in gonads and early embryos as well, it is possible that similar molecular mechanisms are employed to regulate gene expression at these stages [33]. Consistent with this, MKRN2 was recently found to be essential for male fertility in mice [58]. Thus, our study provides a mechanism that explains the role of Mkrn1 in translation and constitutes a solid framework for future investigations deciphering the roles of vertebrate MKRNs in post-transcriptional control of gene expression during gametogenesis and early development.…”
Section: Discussionmentioning
confidence: 76%
“…Since in vertebrates MKRN genes are also highly expressed in gonads and early embryos, it is possible that similar molecular mechanisms are employed to regulate gene expression at these stages (Bohne et al, 2010). Along these lines, MKRN2 was found recently to be essential for male fertility in mice (Qian et al, 2016). Thus, our study provides a solid framework for future investigations deciphering the role of vertebrates MKRN in posttranscriptional control of gene expression during gametogenesis and early development.…”
Section: Discussionmentioning
confidence: 64%
“…59 Interestingly, studies using a Mkrn2 knockout (KO) mouse model reported a role of Mkrn2 in male fertility. 56 While male and female Mkrn2 KO animals were viable with no apparent developmental abnormalities, the mutant animals showed a decrease in body weight. Female Mkrn2 KO mice were fertile but had a reduction in their fertility rate.…”
Section: Makorin Ring Finger Proteinmentioning
confidence: 97%
“…45 In adult mice, Mkrn2 mRNA and protein were ubiquitously expressed at low levels in various tissues (brain, thymus, heart, lung, liver, spleen, kidney, ovary, uterus, and seminal vesicle) with more specific, high expression in the testis. 56 The first study to investigate Mkrn2 function reported that, in Xenopus, Mkrn2 played a negative role in neurogenesis via PI3K/Akt signaling and was essential for proper embryonic neural development. 57 The third C3H zinc finger, Cys-His motif, and C3HC4 RING zinc finger domains were indispensable for this inhibitory effect of Mkrn2 on neurogenesis.…”
Section: Makorin Ring Finger Proteinmentioning
confidence: 99%
See 1 more Smart Citation